Over Capasity as an Opportunity fot the Directorate General of Correctors In Optimizing Revitalization - Rokhman, Fatkhur (Universitas Islam Negeri Walisongo Semarang, 2020)
Overcapacity is a condition in which a building is overloaded. Lots of riots or problems in prisons are caused by overcapacity. Therefore it is necessary to handle and treat overcapacity in prisons which initially became a problem and a threat that could create a potential opportunity in the development and implementation of correctional revitalization. The method used in the making of this journal uses descriptive qualitative research methods. By using secondary data sources, using literature study data collection techniques, and performing data analysis techniques in the form of collecting data, reducing data, presenting data, and concluding data so that it is easy to understand. In Correctional Revitalization, the condition of overcapacity in prisons can be used as an opportunity by placing inmates who have passed the assessment to be placed in minimum security prisons to be optimized or empowered through self-supporting programs such as training in plantations, fisheries, creative crafts, animal husbandry and agriculture and for personality development such as education.[]Overkapasitas merupakan suatu kondisi dimana di dalam sebuah bangunan mengalami kelebihan muatan. Banyak sekali kejadian kerusuhan atau masalah di dalam Lapas di sebabkan karena overkapasitas. Oleh karena itu perlu adanya penanganan dan pengolahan overkapasitas dalam Lapas yang awalnya menjadi masalah dan ancaman bisa menjadikan peluang yang potensial dalam pembinaan dan pelaksanaan revitalisasi pemasyarakatan. Metode yang digunakan dalam pembuatan Jurnal ini, menggunakan metode penelitian kualitatif deskriptif. Dengan menggunakan sumber data sekunder, menggunakan teknik pengumpulan data studi pustaka, dan melakukan teknik analisis data berupa mengumpulkan data, mereduksi data, menyajikan data, dan menyimpulkan data sehingga mudah dipahami. Dalam Revitalisasi Pemasyarakatan, kondisi overkapasitas dalam Lapas bisa dimanfaatkan menjadi sebuah peluang dengan menempatkan narapidana yang telah lulus assessment untuk di tempatkan ke dalam Lapas minimum Security untuk kemudian dioptimalkan atau diberdayagunakan melalui program pembinaan kemandirian seperti pelatihan perkebunan, peikanan, kerajinan kreatif, peternakan, dan pertanian dan untuk pembinaan kepribadian seperti pendidikan.